2014
DOI: 10.3389/fmicb.2014.00326
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-fixing Rhizobium-legume symbiosis: are polyploidy and host peptide-governed symbiont differentiation general principles of endosymbiosis?

Abstract: The symbiosis between rhizobia soil bacteria and legumes is facultative and initiated by nitrogen starvation of the host plant. Exchange of signal molecules between the partners leads to the formation of root nodules where bacteria are converted to nitrogen-fixing bacteroids. In this mutualistic symbiosis, the bacteria provide nitrogen sources for plant growth in return for photosynthates from the host. Depending on the host plant the symbiotic fate of bacteria can either be reversible or irreversible. In Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 45 publications
1
67
0
4
Order By: Relevance
“…Taken together, this horizontal transfer suggests that little coevolution may be needed for the formation of novel symbiosis. However, in some plant-rhizobia or -mycorrhizal associations, the symbiont phenotype can vary substantially among hosts, and the outcome of the association is determined by the interaction of host and symbiont-derived factors (34)(35)(36)(37)(38). Similarly, a synergistic interplay between host and symbiont components mediates the initiation and persistence of the bobtail squid-Vibrio fischeri symbiosis (39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…Taken together, this horizontal transfer suggests that little coevolution may be needed for the formation of novel symbiosis. However, in some plant-rhizobia or -mycorrhizal associations, the symbiont phenotype can vary substantially among hosts, and the outcome of the association is determined by the interaction of host and symbiont-derived factors (34)(35)(36)(37)(38). Similarly, a synergistic interplay between host and symbiont components mediates the initiation and persistence of the bobtail squid-Vibrio fischeri symbiosis (39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…The large size of the NCR family and the limited sequence homology among its members hinder efforts to generalize their role in the symbiosis. Their sequence diversity and distinct temporal and spatial expression patterns have led to the suggestion that they may perform diverse functions, with different bacterial targets and modes of action (9), but direct proof of functional diversity is still lacking.…”
mentioning
confidence: 99%
“…Interestingly, in contrast to most AMP family members, a majority of these peptides are anionic or neutral (Durgo et al, 2015), and they were suggested to neutralize the toxic activity of cationic NCRs. However, although cationic NCRs display in vitro antimicrobial activity, it is doubtful that they exert this activity in vivo, as peptide concentrations in nodules are lower than those used in in vitro assays Tiricz et al, 2013;Maróti and Kondorosi, 2014). Instead, they are essential for bacteroid differentiation and for maintenance of their bacterial endosymbionts Farkas et al, 2014;Penterman et al, 2014).…”
Section: Cysteine-rich Peptidesmentioning
confidence: 99%